Optical Coherence Tomography of Bilateral Nanophthalmos with Macular Folds and High Hyperopia - Firat Helvacioglu; Ziya Kapran; Sadik Sencan; Murat Uyar; Ozlem Cam (Case Reports in Ophthalmological Medicine)
Importance. There is a conflict about the content of the macular folds in nanophthalmic eyes in the literature. Our study clearly demonstrated that papillomacular folds seen in nanophthalmos or posterior microphthalmos were only composed of neurosensory retina without involvement of retinal pigment epithelium and choroid. Observations. This is a report of two consecutive nanophthalmic patients with macular folds at Maltepe University School of Medicine, Department of Ophthalmology, from January to June 2012. Anterior segment dimensions were near normal. The axial lengths of the eyes were short with markedly shortened posterior segment. A macular fold extending from the center of the fovea towards the optic nerve head was present in all eyes. Optic coherence tomography clearly demonstrated that folds were only composed of neurosensory retina. Binocular visual acuities and refractive errors of the cases were 0.3, 0.2 and +16.00, +15.75 diopters, respectively. Conclusions and Relevance. Our study proposes a surgical option to treat these folds like serous retinal detachments by showing the true content of the folds, although there is not any surgical operation accepted for this condition yet. Further studies dealing with the surgical interventions of these folds should be performed to support this option.